2020
DOI: 10.3390/molecules26010067
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant and Anticancer Activities of Leptocarpha rivularis DC Flower Extracts

Abstract: An evaluation of antioxidant and anticancer activity was screened in Leptocarpha rivularis DC flower extracts using four solvents (n-hexane (Hex), dichloromethane (DCM), ethyl acetate (AcOEt), and ethanol (EtOH)). Extracts were compared for total extract flavonoids and phenol contents, antioxidant activity (2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), ferric reducing antioxidant potential (FRAP), total reactive antioxidant properties (TRAP) and oxygen radical absorbance capacity (ORAC)) across a determined v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…The absorbances were measured in the spectrophotometer at a wavelength of 430 nm. Each extract was analyzed in triplicate and the results were expressed in mg quercetin (QE)/g dry weight, based on a calibration curve [30].…”
Section: Determination Of Total Flavonoidsmentioning
confidence: 99%
“…The absorbances were measured in the spectrophotometer at a wavelength of 430 nm. Each extract was analyzed in triplicate and the results were expressed in mg quercetin (QE)/g dry weight, based on a calibration curve [30].…”
Section: Determination Of Total Flavonoidsmentioning
confidence: 99%
“…The chemical composition of extracts of L. rivularis has been extensively studied and it is well established that they contain sesquiterpene lactones, of which LTC is the major component [5,6,30,31]. On the other hand, as the phytochemical composition of plants propagated under in vitro conditions could vary due to controlled cultivation conditions, it becomes necessary to determine the composition of extracts obtained from propagated explants and callus generated in vitro.…”
Section: Phytochemical Analysis Of Extractsmentioning
confidence: 99%
“…In previous work, it was shown that both LTC and extracts of L. rivularis exhibit antiproliferative activity against different cancer cell lines [5,6,8,10]. In this work, the cytotoxicity of extracts, obtained from in vitro-propagated plants of L. rivularis, was evaluated by using cancer and normal cell lines, namely, HeLa (cervical adenocarcinoma) and CCD841/CoN (colon epithelium non-cancer cell line), respectively.…”
Section: Asseessment Of Biological Activity Of In Vitro Plant Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used ancestrally by people of the Mapuche ethnic group to treat gastrointestinal ailments [ 28 ]. L. rivularis produces a variety of bioactive compounds, including a group of molecules termed sesquiterpene lactones (SLs) [ 29 ]. SLs have attracted the attention of researchers for exhibiting anticancer, antifungal, anti-inflammatory, antimicrobial, and antioxidant activities [ 30 ].…”
Section: Introductionmentioning
confidence: 99%